Adjusting the interfacial adhesion via surface modification to prepare high-performance fibers - Ning Han; Xiaolin Zhao; Vijay Kumar Thakur (Nano Materials Science, 2023)
Ultra-high molecular weight polyethylene (UHMWPE) fiber is a new kind of high-performance fiber. Due to its excellent physical and chemical characteristics, it is widely used in various fields. However, the surface UHMWPE fiber is smooth and demonstrates no-polar groups. The weak interfacial adhesion between fiber and resin seriously restricts the applications of UHMWPE fiber. Therefore, the surface modification treatments of UHMWPE fiber are used to improve the interfacial adhesion strength. The modified method by adding nanomaterials elucidates the easy fabrication, advanced equipment and proper technology. Thus, the progress of UHMWPE nanocomposite fibers prepared via adding various nanofillers are reviewed. Meanwhile, the effects of other various methods on surface modification are also reviewed. This work advances the various design strategies about nano technologies on improving interfacial adhesion performance via treatment methodologies.